The schistosome oesophageal gland: initiator of blood processing. - Xiao-Hong Li; William de Castro-Borges; Sophie Parker-Manuel; Gillian M Vance; Ricardo Demarco; Leandro X Neves; Gareth J O Evans; R Alan Wilson (Public Library of Science (PLoS), 2013)
BACKGROUND: Although the ultrastructure of the schistosome esophageal gland was described >35 years ago, its role in the processing of ingested blood has never been established. The current study was prompted by our identification of MEG-4.1 expression in the gland and the observation of erythrocyte uncoating in the posterior esophagus. METHODOLOGY/PRINCIPAL FINDINGS: The salient feature of the posterior esophagus, characterized by confocal and electron microscopy, is the enormous increase in membrane surface area provided by the plate-like extensions and basal invaginations of the lining syncytium, with unique crystalloid vesicles releasing their contents between the plates. The feeding process was shown by video microscopy to be divided into two phases, blood first accumulating in the anterior lumen before passing as a bolus to the posterior. There it streamed around a plug of material revealed by confocal microscopy as tethered leucocytes. These were present in far larger numbers than predicted from the volume of the lumen, and in varying states of damage and destruction. Intact erythrocytes were detected in the anterior esophagus but not observed thereafter, implying that their lysis occurred rapidly as they enter the posterior. Two further genes, MEGs 4.2 and 14, were shown to be expressed exclusively in the esophageal gland. Bioinformatics predicted that MEGs 4.1 and 4.2 possessed a common hydrophobic region with a shared motif, while antibodies to SjMEG-4.1 showed it was bound to leucocytes in the esophageal lumen. It was also predicted that MEGs 4.1 and 14 were heavily O-glycosylated and this was confirmed for the former by 2D-electrophoresis and Western blotting. CONCLUSIONS/SIGNIFICANCE: The esophageal gland and its products play a central role in the processing of ingested blood. The binding of host antibodies in the esophageal lumen shows that some constituents are antibody targets and could provide a new source of vaccine candidates.